Online sex work: Professionalizing the industry amidst the Covid-19 lockdown - Juliet Eileen Joseph (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This study contributes to the relatively limited body of knowledge regarding sex work and  the limited progress in the decriminalization  of sex work as paid labour, which impacts the inclusion of sex workers in epidemic response. Since sex workers form part of vulnerable populations, the Covid 19 pandemic has also affected their socioeconomic status, further displacing them into poverty and exacerbate existing inequalities. In particular, South Africa has made great progress towards equality for all groups, such as the legalization of same-sex marriages in its Constitution. In spite of this, sex workers remain an underrepresented group of workers, since sex work is not legalized as a profession, which negatively impacts their representivity in epidemic responses. In this context, there is an abundance of literature on sex work, which has led to the development of theory and conceptual frameworks. Within the context of the Covid 19 pandemic, this study presents the context of sex workers in South Africa. Additionally, the study examines the barriers faced by sex workers as well as their legalization and professionalization as workers. There are numerous instances of the violation of sex workers and given that sex work isn’t legalized they are not protected by the law and often find themselves confronted with criminals who break laws against them. Furthermore, the study critically examines how sex workers have professionalized their industry during the Covid 19 pandemic and in the age of 4IR. Last but not least the study concludes on the challenges that hinder the legalization of sex workers  in South Africa. It would seem that the state should consider reviewing how it caters to severely socially excluded populations if they fail to represent, participate, or protect sex workers.